2009
DOI: 10.1111/j.1600-0714.2009.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery system for oral cancer therapy using sonoporation

Abstract: Ultrasound-mediated destruction of microbubbles has been proposed as an innovative non-invasive drug delivery system for cancer therapy. We developed a specific drug delivery system for squamous cell carcinoma that uses sonoporation with the anti-epidermal growth factor receptor (EGFR) antibody. Administration of a low dose of bleomycin (BLM) by sonoporation with the anti-EGFR antibody produced a marked growth inhibition of Ca9-22 cells in vitro. In addition, scanning electron microscopic analysis revealed app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The resulting microbubble formulation efficiently bound nearly 100 μg DNA per 1 × 10 9 microbubbles, which is significantly higher compared with reports of others (Hayashi et al 2009; Maeda et al 2009). Importantly, unlike naked plasmids, which are quickly degraded by blood DNAses upon vascular administration, our data showed that the plasmid on the microbubble surface was shielded from digestion by DNAse.…”
Section: Discussionmentioning
confidence: 56%
“…The resulting microbubble formulation efficiently bound nearly 100 μg DNA per 1 × 10 9 microbubbles, which is significantly higher compared with reports of others (Hayashi et al 2009; Maeda et al 2009). Importantly, unlike naked plasmids, which are quickly degraded by blood DNAses upon vascular administration, our data showed that the plasmid on the microbubble surface was shielded from digestion by DNAse.…”
Section: Discussionmentioning
confidence: 56%
“…With its noninvasive and steerable nature, US is a useful tool in combined treatment with anti-cancer agents. Sonoporation has been associated with enhanced drug delivery in chemotherapy in primary studies concerning cutaneous melanoma (19,20) lymphoma (21) and oral cancer (22,23). It appears that there have been few studies focusing on PCa and combination therapy, and only a small number on the enhancement of permeability in vivo (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, Maeda et al . showed that sonoporation of anti-EGFR antibody in vitro makes it possible to administer bleomycin into cells more efficiently and specifically, showing an application for cancer therapy in squamous cell carcinoma [5]. It could be possible to decrease effectiveness of the antibody when internalized if that particular antibody requires an extracellular interaction to begin its cascade of events (for example, TRA8 and targeting the DR-5 receptor to kill tumor cells) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although antibodies circulate for weeks, if blood flow to the tumor is limited, those that do not reach their intended target are metabolized by the liver before reaching the cancer [3]. Although targets for antibody therapy are extracellular, previous in vitro studies have shown that using microbubble-mediated ultrasound therapy can increase localized effectiveness of cancer therapy [5]. …”
Section: Introductionmentioning
confidence: 99%